2005
DOI: 10.1159/000084633
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Medication Use among Adolescents in Kuwait

Abstract: Objective: The objectives of this study were to describe and examine the pattern of medication use, including age and gender differences among adolescents in Kuwait, and to establish the sources of information on medicines in this age group. Subjects and Methods: A cross-sectional survey of 1,110 male and female students (14–21 years) from 10 randomly selected public schools in Kuwait was conducted.The prevalence of self-medication was estimated.Results: The prevalence of self-medication among the high school … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
95
7
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(133 citation statements)
references
References 7 publications
(7 reference statements)
25
95
7
3
Order By: Relevance
“…19,20 We believe it is due to the frequent pain associated with menstrual cycle. On the other hand we found that there is no statistical significant difference between gender and other drugs used which agrees with study of An-Najah National University palatine.…”
Section: Discussionmentioning
confidence: 95%
“…19,20 We believe it is due to the frequent pain associated with menstrual cycle. On the other hand we found that there is no statistical significant difference between gender and other drugs used which agrees with study of An-Najah National University palatine.…”
Section: Discussionmentioning
confidence: 95%
“…The prevalence has been announced to be approximately 3% in Europe [8]. Conversely, there is an enormous increase in Asia, with the values around 4-75%, which may reach 80.4%in college students [9] or even 92% in Kuwait [10].…”
Section: Introductionmentioning
confidence: 99%
“…Second year students practice self-medication more often. Previous Studies on self-medication have reported various prevalence figures, ranging from 26.2% [11] to as high as 92% [14]. The commonest illnesses that led to self-medication in this study were usually self-limiting "minor illnesses" that have been widely reported in studies on self-medication as the most common indications [2,10].…”
Section: Discussionmentioning
confidence: 45%